2021
DOI: 10.15625/2615-9783/16328
|View full text |Cite
|
Sign up to set email alerts
|

Neo-deterministic seismic hazard maps of Kosovo

Abstract: Kosovo is one of the most seismically active regions in Europe, lying within the Alpine-Mediterranean tectonic belt. Historical records for the region show several catastrophic earthquakes with epicentral intensity IX (MCS). However, due to Kosovo’s high population density, high prevalence of traditional construction, and insufficient enforcement of building codes, Kosovo is vulnerable to earthquake damage. In this study, we present earthquake hazard maps for bedrock conditions in Kosovo based on the well-know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Rugarli et al ( 2019) applied M design to the rest of the Italian territory considering only seismogenic nodes and obtained hazard maps in agreement with those based on seismogenic zones and the CPTI04 catalog. Brandmayr et al (2021) showed that the application of M design (at 1 Hz cut-off frequency) in Kosovo gives hazard levels consistent with 10 Hz cut-off frequency computation, which needs a knowledge of sources and structures with a detail not available for the study area. Therefore, we consider the ground motion maps obtained applying M design the most, now possible, reliable advancement in the understanding of the seismic hazard of the area.…”
Section: Resultsmentioning
confidence: 99%
“…Rugarli et al ( 2019) applied M design to the rest of the Italian territory considering only seismogenic nodes and obtained hazard maps in agreement with those based on seismogenic zones and the CPTI04 catalog. Brandmayr et al (2021) showed that the application of M design (at 1 Hz cut-off frequency) in Kosovo gives hazard levels consistent with 10 Hz cut-off frequency computation, which needs a knowledge of sources and structures with a detail not available for the study area. Therefore, we consider the ground motion maps obtained applying M design the most, now possible, reliable advancement in the understanding of the seismic hazard of the area.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is a young method compared with PSHA, NDSHA is being extensively applied and tested in many countries since a couple of decades, e.g., Croatia [59], Kosovo [60], northern Morocco [61], Egypt [62], India [58,63], North China [64], Southwest China [45]. As shown in Figure 3a, the standard computation scheme contains a wealth of deterministic inputs, such as historical and instrumental earthquake catalogues, seismogenic nodes, seismogenic zones, focal mechanisms, and regional polygons equipped with characteristic structural models (mechanical properties) are the input datasets for standard NDSHA computations.…”
Section: Ndsha Approach: Methodologymentioning
confidence: 99%